Leśnictwo i produkcja drzewna w Demokratycznej Republice Wietnamu - Nam, Nguyen van (Wydział Prawa i Administracji UAM, 1971)
Against the total area of 158.75 thousand sq. km. are woodland, of which 56.2 thousand sq. km. are forests available for use. In the afforested area there are 200 genera of trees divided into 12 000 species. Some of the species belong to the most precious in the world. Forestry is a vital part of the economy of democratic Viet-Nam. It supplies the building trade and other industries with raw materials. The forests screent the cultivated land and the villages from winds and moderate the climate. The forests are developed by state farms and by co-operative farms. The proportions of the natural forests and the planted ones are constantly changing to the advantage of the latter. Planting trees is one of the nation-wide activities. In the years 1960 -1967 a total of 830.000 ha was planted with varius genera and species of trees. In the same period the number of trees planted per year rose sevenfold. Based on the gained timber several well equipped industrial enterprises have been established. The lead is taken by timber intended for shipbuilding, farm machinery, sleepers and pit props. Paper is made of bamboo cane.
Forestry and Timber Production in the Democratic Republic of Viet-Nam